Power Relations Reflected In George Bernard Shaw's Drama Caesar And Cleopatra (1898):A Sociological Approach - Widiawati, Faradita, Dr. M. Thoyibi, M.S (2017)
SUMMARY FARADITA WIDIAWATI / A320130124. POWER RELATIONS REFLECTED IN GEORGE BERNARD SHAW'S DRAMA CAESAR CLEOPATRA (1898): A SOCIOLOGICAL APPROACH. RESEARCH PAPER. SCHOOL OF TEACHER TRAINING AND EDUCATION, MUHAMMADIYAH UNIVERSITY OF SURAKARTA. JUNI, 2017. This study is aimed to show power relations of Caesar and Cleopatra by using sociological approach. It is done by establishing three objectives: the first is to identify indicators of power relations in the literary work, second is to describe how power relations portrayed in the literary work and the last is to reveal why George Bernard Shaw addressed power relations related the drama. The type of this research is qualitative research. In this method, the writer uses two types of data sources: those are primary and secondary data sources. The primary data sources are the study of Caesar and Cleopatra drama, the script written by George Bernard Shaw. The secondary data sources are taken from some books and website. The result of the study shows that power relations reflected in George Bernard Shaw's drama Caesar and Cleopatra is through the indicators, character and characterization, plot and theme. Caesar and Cleopatra show the role of every member in the environment especially in community and public relations in shaping the major of sociological. Keywords: Caesar and Cleopatra, power relations, throne